Value creation on Norway’s green gold : an analysis of policy formulation and implementation in the field of nature conservation. - Fedreheim, Gunn Elin (Universitetet i Nordland, 2013)
Doctoral thesis (Ph.D.) – University of Nordland, 2013 This dissertation’s puzzle is to ascertain why a policy from 2003 aimed at increasing nature-based tourism in Norway has not yet lead to changes for tourism operators. The underlying expectations were that such a policy decision, which marked a shift in Norwegian environmental politics from a conservation path to a conservation-and-use path, would lead to institutional changes or the crafting of new institutions. Hence, this dissertation aims at answering the question "What facilitates or hinders whether a policy decision in the end leads to institutional change?" The purpose of investigating this question was to understand why this policy did not lead to changes for tourism operators, as well as to describe how a policy decision relates to an institutional change and vice versa. The policy studied here is called the Mountain Text (Fjellteksten) and aims to increase nature-based tourism in protected areas in Norway. Internationally a recent acknowledgment of conservation’s shortcomings resulted in a "new conservation paradigm" which Norway responded to with the Mountain Text. One of the goals of the Mountain Text was to increase the legitimacy of protected areas, because prior to 2003 Norwegians had a negative attitude toward them. In this dissertation, policies are understood as series of dynamic decisions that are formulated and influenced by other policies. Policy making is described as a cycle in which three overlapping and interdependent activities take place: policy formulation, policy decision, and policy implementation. Policy making does, in many cases, lead to institutional changes, or may come as a result of institutional changes. Institutions are here understood as Elinor Ostrom defined them: "the prescriptions that humans use to organize all forms of repetitive and structured interactions including those within families, neighborhoods, markets, firms, sports leagues, churches, private associations, and governments at all scales." Institutions ...